Collective action, incentives and social welfare : an analysis of South African policy forums - Sellars, Sean Christian Maurice (School of Economics, 2016)
This paper is concerned with the analysis of South African policy making forums. It attempts to develop an understanding of how such forums might contribute to the welfare of South African society, and what can be done to enhance this contribution. The widespread emergence of policy making forums in South Africa has not gone unnoticed. Much local literature has been produced in recent years on the issue (Baskin, 1993; Maree, 1993; Schreiner, 1994; Nattrass, 1994). All of these contributions adopt the framework of "neo-corporatism" in their analysis. By contrast, this paper is grounded in the theory of public choice. The concept of "neo-corporatism" has been developed in a body of international literature concerned with the institutional structures through which policy was developed and implemented in countries such as Austria and Sweden in the post war period (Grant, 1985). These institutional structures evolved out of the imperatives of post-war reconstruction and the balance of power between labour, capital and state. The prefix neo- is used to distinguish the institutional arrangements in these social democracies from those in place in fascist Italy which have been referred to as corporatist. There is much confusion over the exact meaning of "neo-corporatism", but there seems to be some agreement that it centrally involves the relationship between the state and organised interests such as business and labour. In the countries identified as neo-corporatist, this relationship was structured in such a way as to influence the behaviour of each of these parties towards the attainment of national objectives such as growth and low unemployment (ibid:4). There are two reasons why I have chosen not to use neo-corporatism as the means of analysis in this paper. Firstly, the thinking around the concept has been developed inductively from the experiences of particular societies, but a plausible deductive theory of what transpired in these societies has not been forthcoming (Olson, 1986). To use a crude example, it might thus be said that while we can observe that Sweden had very low levels of unemployment for most of the post-war period and that Swedish policy making was characterised at the time by a particular type of interaction between government, labour and business, neo-corporatist theory does not offer a robust (deductive) argument of why certain policy making institutions led to particular desirable social outcomes. In other words, the understanding of the causal relationship between existing institutions and social outcomes remains undeveloped. The second reason for not using a neo-corporatist framework in the analysis which follows is that the political and economic conditions in contemporary South Africa are very removed from those of European neo-corporatist countries, and thus inductive theory based on the European experience is not of much use. In particular, as is argued in Chapter Two, the state, seen as the primary factor directing the policy making process in neo-corporatist theory, has played a very ambiguous role in the South African experience of forum based policy making. As South African policy forums have arisen during a period of political transition, the government has had neither the confidence nor the legitimacy to play the directing role which has characterised episodes of neo-corporatism in other countries. The paper is divided into two chapters. The first considers a deductive theory of interest group behaviour developed from the literature of public choice and the second applies this to South Africa's recent experience of policy forums. Most public choice literature is concerned with the state, as processes influencing government such as voting and lobbying are seen as a central means through which individuals take collective action. In addition, it is through government bureaus that the goods and services demanded through this action are supplied (Mueller, 1976; Wolf, 1979). As stated, the emphasis in what follows is slightly different in that the activities of interest groups is the major subject of consideration.